Analysis of DAT Combined with the VSD Technique in Wound Repair of Rats and Its Effect on Inflammatory Factors. (20th August 2022) - Sun, Xiaochen; Xu, Chengxin; Lian, Juan; Song, Mei
Abstract : The clinical efficacy of decellularized adipose tissue (DAT) combined with vacuum sealing drainage (VSD) in the treatment of wound healing in rats is investigated, and the changes of inflammatory factors are analyzed. The tissue defect model of SD (Sprague-Dawley) rats is established and divided into the combined group ( n  = 12) and the control group ( n  = 12) according to different treatment methods. The control group is treated with a single VSD technique, and the combined group is treated with DAT on the basis of the control group. The wound healing time of the two groups is observed. Wound tissue is collected 1 day, 10 days, 20 days, and 30 days after treatment, and neutrophil infiltration is observed by HE (hematoxylin-eosin) staining. The expression changes of IL-6 and IL-13 at each time point before and after treatment are compared. Histological observation shows that the cell infiltration is reduced in both groups, and the wound repair in the combined group is better than that in the control group. The experimental results show that the DAT combined with the VSD technique can further speed up wound healing and reduce inflammation in rats.